Relationships between motor abilities and volleyball performance skills in 15-year-old talent-identified volleyball players - Mroczek, D.; Superlak, E.; Kawczynski, A.; Chmura, J. (Baltic Journal of Health and Physical Activity, 2017)
The aim of this study is to determine synergistic motor outcomes understood as sets of mutually dependent players` motor abilities affecting the efficacy of performance skills of young volleyball players.